Integration of an Energy Storage in Connection with the Combustion Chamber of a Diesel Engine to Reduce the NOx Emission - Dion Arman Lilipaly; Karsten Wehner; Steffen Loest (Institut Teknologi Sepuluh Nopember, 2018)
This thesis is focusing on how to reduce the NOx emission since it has been an issue in all over the world. An idea that reduced the combustion temperature by integrating an external chamber connected with the combustion chamber as a temporary energy storage. This method is implementing the pressure-temperature law, where the pressure is reduced by expanding the volume that resulted a temperature decreased. The aims of this study were to make a feasibility study of the previous invention, a combustion model simulation and technical drawings design of the external chamber. The simulation model involves an analysis of how the temporary energy stored effected the combustion temperature and calculating the pipeline losses. The results showed that by installing the external chamber, the combustion temperature was reduced significantly by 6.15% for the burn zone and 17.8% for the unburn zone. Furthermore, a comparison of the pipeline heat loss showed that an insulated pipe saved 94.1% more heat energy than the uninsulated. The important factor in designing the external chamber were the spring deflection and piston bore. An analysis shown that the larger the deflection and piston bore, the bigger the pressure drop would be which is why an optimization of those factors were needed.